2019
DOI: 10.3389/fnins.2019.00084
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Integrated Functional Near-Infrared Spectroscopy (fNIRS) and Transcranial Magnetic Stimulation (TMS) Studies

Abstract: Background: The capacity for TMS to elicit neural activity and manipulate cortical excitability has created significant expectation regarding its use in both cognitive and clinical neuroscience. However, the absence of an ability to quantify stimulation effects, particularly outside of the motor cortex, has led clinicians and researchers to pair noninvasive brain stimulation with noninvasive neuroimaging techniques. fNIRS, as an optical and wearable neuroimaging technique, is an ideal candidate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 88 publications
1
57
0
Order By: Relevance
“…PET scanning has demonstrated similar findings with widespread increases in regional cerebral activation. 35 The impact of TMS on fNIRS responses was reviewed by Curtin et al, 74 in which a number of studies cited demonstrated increased HbO 2 with TMS, a finding again confirmed in PET scanning. 75 The increase in HbO 2 is generally thought to be due to an indirect "metabolic hypothesis" whereby an increase in neuronal activation results in additional energy and oxygen consumption, which may explain the brief initial drop in HbO 2 recorded in some studies.…”
Section: Discussionmentioning
confidence: 98%
“…PET scanning has demonstrated similar findings with widespread increases in regional cerebral activation. 35 The impact of TMS on fNIRS responses was reviewed by Curtin et al, 74 in which a number of studies cited demonstrated increased HbO 2 with TMS, a finding again confirmed in PET scanning. 75 The increase in HbO 2 is generally thought to be due to an indirect "metabolic hypothesis" whereby an increase in neuronal activation results in additional energy and oxygen consumption, which may explain the brief initial drop in HbO 2 recorded in some studies.…”
Section: Discussionmentioning
confidence: 98%
“…The physiological techniques also require a smaller sample size to estimate reliable cognitive load states (Tran et al, 2007). Physiological sensors, such as electroencephalogram (EEG), heart rate variability (HRV), eye response measurement, functional magnetic resonance imaging (fMRI), and functional near-infrared spectroscopy (fNIRS) are most commonly used for the monitoring of the MWL (Hong and Santosa, 2013;Tong et al, 2016;Curtin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Functional near-infrared spectroscopy (fNIRS) is a neuroimaging technique that has several advantages including being portable and non-invasive. It has a wide application in the field of rehabilitation (e.g., gait rehabilitation, cognitive assessment, brain-machine interface, a combined modality with electroencephalography, and influence of external stimulation assessment) and in different populations (e.g., stroke, mild cognitive impairment, Parkinson’s disease; Zafar and Hong, 2016 ; Khan M. J. et al, 2018 ; Khan R. A. et al, 2018 ; Yaqub et al, 2018 ; Bandeira et al, 2019 ; Curtin et al, 2019 ; Ghafoor et al, 2019 ; Li et al, 2019 ; Yang et al, 2019 ). Furthermore, as fNIRS is less sensitive to motion artifact compared with some neuroimaging modalities, real-time cortical activity during movement of proximal joints, such as the shoulder, can be undertaken where the usage of current traditional neuroimaging tools (e.g., fMRI) is limited (Strangman et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%